National resilience in Ukraine's war: insights for Singapore - Ong, Wei Chong (2024)
Ukraine and Ukrainians have demonstrated remarkable resilience in the ongoing war against Russia. The Ukrainian experience provides valuable lessons that Singapore can learn to strengthen national resilience in testing times.